Meningkatkan Perilaku Asertif Peserta Didik Melalui Layanan Bimbingan Kelompok Dengan Metode Role Playing - Cyndi Apriani Sitanggang; Intan Prastihastari Wijaya (CV. ITTC INDONESIA, 2025)
Assertive behavior is the ability to be assertive, refuse without offending the feelings of others and build friendships with others, the environment and the surrounding community. Observations conducted in class X at SMA Ngeri 7 Kediri showed that there were several students who had low / sufficient assertive behavior. This study aims to improve the assertive behavior of students with role playing techniques through group guidance services. The research was conducted in two cycles with a total of three meetings, starting from pre-cycle, followed by cycle I and cycle II. Each cycle consists of 4 stages; planning, implementation, observation, reflection. The research subjects were 7 students of class X-8. The method of this research is descriptive and comparative analysis to compare data before and after action during the implementation of each cycle. The results showed an increase in students' assertive behavior with 32% in the pre-cycle, increasing to 46% in cycle I then continued in cycle II increasing to 62%, these results show that role playing is able to increase the assertive behavior of students.